Parasitic copepods of the common sole, Solea solea (L.), from the Eastern Mediterranean coast of Turkey. - Özak, A.A., I. Demirkale, G.A. Boxshall & M. Etyemez (Systematic Parasitology, 2013)
There is increasing interest in the common sole, Solea solea (Linnaeus), as an alternative fish species in aquaculture in the Mediterranean region, and parasitic copepods are a potential hazard for farmed finfish. This paper provides taxonomic information on two species of sea lice (family Caligidae) collected from S. solea in eastern Mediterranean waters off the Turkish coast. Caligus brevicaudatus A. Scott, 1901 and Caligus apodus (Brian, 1924) were both found and this is the first report of C. brevicaudatus in Turkish waters. The discovery of C. apodus on S. solea is a new host record. Key diagnostic characters of both species are reported, supported by light and scanning electron microscopy observations. During a 12-month survey a prevalence of 28% was recorded for C. brevicaudatus, whereas for C. apodus peak prevalence was much lower (3%).